1999
DOI: 10.1590/s0001-37141999000400003
|View full text |Cite
|
Sign up to set email alerts
|

Production of extracellular lipase by the phytopathogenic fungus Fusarium solani FS1

Abstract: A Brazilian strain of Fusarium solani was tested for extracellular lipase production in peptone-olive oil medium. The fungus produced 10,500 U.L -1 of lipase after 72 hours of cultivation at 25ºC in shake-flask at 120 rpm in a medium containing 3% (w/ v) peptone plus 0.5% (v/v) olive oil. Glucose (1% w/v) was found to inhibit the inductive effect of olive oil. Peptone concentrations below 3% (w/v) resulted in a reduced lipase production while increased olive oil concentration (above 0.5%) did not further stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 19 publications
3
21
2
11
Order By: Relevance
“…This suggests that Aspergillus niger 65I6 produced an alkaline lipase from the Jatropha curcas seed cake medium, contrasting other studies which report that most lipases produced by Aspergillus are acidic (Pera et al, 2006;Shu et al, 2009;Mhetras et al, 2009;Toida et al, 1998). Alkaline lipases have been reported from other strains, however, including Fusarium oxysporum (Prazeres et al, 2006;Rifaat et al, 2010), Fusarium solani (Maia et al, 1999), Penicillum chrysogenum (Cho et al, 2007), and Rhizopus chinensis (Sun and Xu, 2009). The differing characteristics of the Aspergillus niger 65I6 lipase is probably related to the physiology of the microorganism.…”
Section: Partial Purification Of Lipase Using Anion Exchange Chromatomentioning
confidence: 87%
“…This suggests that Aspergillus niger 65I6 produced an alkaline lipase from the Jatropha curcas seed cake medium, contrasting other studies which report that most lipases produced by Aspergillus are acidic (Pera et al, 2006;Shu et al, 2009;Mhetras et al, 2009;Toida et al, 1998). Alkaline lipases have been reported from other strains, however, including Fusarium oxysporum (Prazeres et al, 2006;Rifaat et al, 2010), Fusarium solani (Maia et al, 1999), Penicillum chrysogenum (Cho et al, 2007), and Rhizopus chinensis (Sun and Xu, 2009). The differing characteristics of the Aspergillus niger 65I6 lipase is probably related to the physiology of the microorganism.…”
Section: Partial Purification Of Lipase Using Anion Exchange Chromatomentioning
confidence: 87%
“…Increase or decrease in pH had negative impact on the production of lipase. In another study, Fusariumsolani gave maximum lipase production at pH of 8.6 (Maia et al, 1999).…”
Section: Effect Of Ph Of the Medium On Production Of Lipase -mentioning
confidence: 88%
“…(Elibol and Ozer2000) also reported that main reason for the negative effect of agitation speed might due to the perturbation of protein structure during the biosynthesis of lipase. Agitation rate of 120 rpm was found to give maximum lipase production from Fusarium solani (Maia et al, 1999) and Penicilliumcyclopium (Vanot et al, 2002).…”
Section: Effect Of Ph Of the Medium On Production Of Lipase -mentioning
confidence: 99%
“…Stability at 28˚C was different for xylanase activity (81.2%), and for polygalacturonase was 61% (Figures 3 and 4). For the induction of extracellular enzymes in Fusarium solani, there are few reports of this species in the literature, and there are referred to F. oxysporum or other species [6,7,18], but reports of F. solani were found as a pathogen associated celery in South America [19], infecting asparagus in five municipalities of Guanajuato [20], and vegetable and flower species in Jujuy, Argentina [21], and some different enzymes [10][11][12][13]. But not found any reports of F. solani in tomato, as the strain that was isolated from the culture of Villa de Arista, S.L.P.…”
Section: Induction Of Extracellular Lytic Enzymesmentioning
confidence: 99%
“…It has been reported that F. oxisporum produces a variety of lytic enzymes, which depolymerize all components of plant cell walls, such as cellulose, xylan, pectin, polygalacturonic acids and proteins (extensins); and they have been purified and biochemically characterized as several enzymes, one endopolygalacturonase majority (PG1), two exopolygalacturonase (PG2 and PG3), one endoxylanase (XYL1), one endopectate lyase (PL1) [6,7], seven polygalacturonases of Fusarium species of Pinus pinea [8], and the isolation of differentially expressed genes during interactions between tomato cells and a strain of F. oxysporum [9]. With respect to F. solani, studies have reported the isolation of a novel pectate lyase gene from the phytopathogenic fungus F. solani [10], a F. solani mutant recurring in cutinase activity and virulence [11], extracellular lipase by the phytopathogenic fungus F. solani FS1 [12], and a cellulose of F. solani [13]. Therefore, it is important to try to determine cellulolytic enzymes involved in the pathogenesis of F. solani.…”
Section: Introductionmentioning
confidence: 99%